Literature Review: Keefektifan Monopoli Berbasis Crt untuk Meningkatkan Minat Belajar di Sekolah Dasar - Risma Diah Aulia; Ellianawati Ellianawati; Decky Avrillianda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Students' learning interest in Civics subjects in elementary schools tends to be low due to conventional and less interactive learning methods. This study aims to analyze the effectiveness of CRT (Culturally Responsive Teaching) based monopoly media integration in increasing students' learning interest in the 2015 to 2025 timeframe. The CRT approach emphasizes cultural relevance in learning, allowing students to better understand the material by relating it to their experiences and environment. Sources of information from Google Scholar, Crossreff, and Scopus were analyzed with the help of the Publish or Perish (PoP) application and VoS Viewer to display visual data analysis results. A total of 2026 articles were analyzed and 4 clusters were obtained that included the effectiveness of monopoly media, the variety of topics studied, the objectives of learning outcomes that showed a close relationship between the effectiveness of CRT-based monopoly on increasing students' interest in learning. Civics learning using CRT-based monopoly media has not been studied specifically, but the research results show that there are many opportunities to optimize CRT-based monopoly media in this topic.